The usage of water and drinking water sludge as a mass concrete / Zazuwa Idayu Zulkifli - Zulkifli, Zazuwa Idayu (Faculty Of Civil Engineering, 2007)
This study has been focus on producing on concrete specimens by adding the drinking water treatment sludge and wastewater sludge as an additive for concrete mix. The sludge used is a dry sludge from Batu Fringgi water treatment plant and Mak Mandin wastewater treatment plant. With the addition of difference proportion (10%, 20%, 30%, 40% and 50%) of sludge as a fine aggregate replacement to amount of concrete, the compressive strength tests were carried out on cubic specimens at age of 4, 7, 14 and 28 days. The results shows that the concrete specimens containing drinking water sludge and wastewater sludge yield lowers compressive strength compare to reference concrete. The strength produced does not achieving the target strength of concrete.